Efficiency, operational stability and biofouling of novel sulfomethylated polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene cation exchange membrane in microbial fuel cells - Koók, László; Žitka, Jan; Szakács, Szabolcs; Rózsenberszki, Tamás; Otmar, Miroslav; Nemestóthy, Nándor; Bélafi-Bakó, Katalin; Bakonyi, Péter (Bioresource technology, 2021)
In this work, a novel cation exchange membrane, PSEBS SU22 was deployed in microbial fuel cells (MFCs) to examine system efficacy in line with membrane characteristics and inoculum source. It turned out that compared to a reference membrane (Nafion), employing PSEBS SU22 resulted in higher current density and electricity generation kinetics, while the electron recoveries were similar (19-28%). These outcomes indicated more beneficial ion transfer features and lower mass transfer-related losses in the PSEBS SU22-MFCs, supported by membrane water uptake, ion exchange capacity, ionic conductivity and permselectivity. By re-activating the membranes after (bio)foulant removal, PSEBS SU22 regained nearly its initial conductivity, highlighting a salient functional stability. Although the particular inoculum showed a clear effect on the microbial composition of the membrane biofouling layers, the dominance of aerobic species was revealed in all cases. Considering all the findings, the PSEBS SU22 seems to be promising for application in MFCs.
Keywords: alkeny; Polystyrenes; Cations; Microbial fuel cell; kationty; Ion exchange membrane; polyethylen; polystyreny; Ethylenes; Biofouling; ethyleny; Electricity; Bioelectric Energy Sources; Polyethylene; Alkenes; Microbial consortia analysis; zdroje bioelektrické energie; elektrody; elektřina; Electrodes; Membrane characterization; bioznečištění